Practical Geophysical Technology and Application for Lithological Reservoirs - Wang, Huandi; Li, Ming; Wu, Yadong; Gao, Jianrong (SpringerBriefs in Petroleum Geoscience & Engineering, Towards Sustainable Geoenergy and Transition to Net Zero, 2022)
VIII, 113 p. 45 illus., 32 illus. in color.